Modelling of metasomatosis in radiogenic rocks as a factor of transformation of their properties - V.A. Baranov; L.F. Mametova; V.Yu. Korovin (Геофизический журнал, 2020)
The development of nuclear technologies, their use in industry and economic activities of the state determine the relevance of this work. The emergence of problems in the implementation of technologies requires the scientific support of the safe extraction of uranium raw materials. Given the need for their solution, the goal of this article was to conduct applied research on the impact of geological processes (metasomatic and tectonics) on the conversion of uranium into rocks, verification of the behavior of uranium in different conditions which are close to nature ones. To achieve the goal, theoretical, experimental and analytical methods have been applied. Based on the analysis of modern scientific views, it was established that the change in geological conditions affects the minerals of any rocks and ores, in particular — on uranium. Hydrothermal, metasomatic and hypergene processes transform the basic characteristics of minerals (composition, structure, geochemical stability, density, etc.). There are dissolution and migration of mineral and ore components, there are new minerals. The experiment, simulating the metasomatic processes in granites and crystalline shales, was carried out. Supplements of fluoride-ammonium fluoride and urea nitrate were used to intensify the process of destroying the structure of minerals from persistent rocks with uranium. The experimental conditions are: a) static and dynamic ones; b) change in concentration and rate of reagent supply. It was established that uranium carriers are accessory minerals and albitites which are the product of metasomatosis of granites, migmatites, and other rocks. Two stages of albitization are revealed, with which the distribution and concentration of uranium are related. In tectonic zones, repeated activation of movements was detected by microdeformations of minerals. It was found out that dynamic conditions and changes in the concentration of reagents contributed to the loss of mass of samples. Consequently, geological processes regulate geochemical transformations in rocks, which result both in the enrichment of uranium and in its removal in conditions of changing the concentration of solutions and tectonic activation.